U-shaped Vortex Structures in Large Scale Cloud Cavitation. (November 2015) - Cao, Yantao; Peng, Xiaoxing; Xu, Lianghao; Hong, Fangwen
Abstract: The control of cloud cavitation, especially large scale cloud cavitation(LSCC), is always a hot issue in the field of cavitation research. However, there has been little knowledge on the evolution of cloud cavitation since it is associated with turbulence and vortex flow. In this article, the structure of cloud cavitation shed by sheet cavitation around different hydrofoils and a wedge were observed in detail with high speed camera (HSC). It was found that the U-shaped vortex structures always existed in the development process of LSCC. The results indicated that LSCC evolution was related to this kind of vortex structures, and it may be a universal character for LSCC. Then vortex strength of U-shaped vortex structures in a cycle was analyzed with numerical results.